2001
DOI: 10.1016/s0378-1097(01)00287-7
|View full text |Cite
|
Sign up to set email alerts
|

The significance of nasal carriage of Staphylococcus aureus as risk factor for human skin infections

Abstract: The present study was designed to investigate the significance and the relationship between nasal carriage of Staphylococcus aureus and staphylococcal skin infections. Thirty-one S. aureus strains, isolated from 12 patients with chronic and recurrent skin infections, one patient with septicemia and one patient with otitis externa were studied. The staphylococcal strains were isolated from the site of infection and from the anterior nares of each patient. The identity of both strains of each pair could be demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…The implementation of a luk-PV test for the diagnosis of S. aureus infection would therefore provide important information for the treating clinician. Our findings are also relevant for therapy, because we and others have shown that the vast majority of patients with chronic furunculosis (87 to 100%) are nasal carriers of their infecting S. aureus strain (10,48,51). To prevent repeated reinfection, the elimination of this S. aureus strain from the whole body as well as the patient's environment should be the aim of therapy for chronic furunculosis (58,61).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The implementation of a luk-PV test for the diagnosis of S. aureus infection would therefore provide important information for the treating clinician. Our findings are also relevant for therapy, because we and others have shown that the vast majority of patients with chronic furunculosis (87 to 100%) are nasal carriers of their infecting S. aureus strain (10,48,51). To prevent repeated reinfection, the elimination of this S. aureus strain from the whole body as well as the patient's environment should be the aim of therapy for chronic furunculosis (58,61).…”
Section: Discussionmentioning
confidence: 64%
“…About 20% of the healthy population are persistent nasal S. aureus carriers (53,57). Patients suffering from chronic furunculosis are usually S. aureus carriers, and skin and nose isolates from a given patient commonly have identical characteristics (10,48,51).…”
mentioning
confidence: 99%
“…While the effects of superantigens ingested through the oral route (e.g., food poisoning) or absorbed through the vaginal mucosa (i.e., menstrual toxic shock syndrome) have been studied (71), the effect of superantigen exposure through the airways has not been explored. This is important because S. aureus and S. pyogenes colonize the upper airways of humans (6,13,97) and act as a major source of infection especially of the respiratory tract (25,91). About 2% of community-acquired pneumonias and up to 10% of hospital-acquired pneumonias are caused by S. aureus (62).…”
Section: Discussionmentioning
confidence: 99%
“…15 These skin particles measuring 10-25 μm and roughly 1 μm thick [2] especially have a lot of staphylococci many people are carriers of. 16,17,18,19 This group of microorganisms is responsible for post-operative wound infections especially in implantation surgery. 15 We didn't find other research related to contamination of sterile instruments during the laying-up process with different air systems or the air quality provided by different systems during this process to compare our study with.…”
mentioning
confidence: 99%